Optimalisasi Kemampuan Penyelesaian Masalah pada Siswa Melalui Penggunaan Website Hooda Math - Tasya; Sirwanti; Aisyah Nursyam; Andi Trisnowali MS (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Problem solving skills in mathematics are still a challenge for students, especially with the limited use of interactive learning media. This community service aims to improve students' problem solving skills through the use of the hooda math website. This activity was carried out at SD Negeri 01 Jatiroyo using the Participatory Action Research (PAR) approach which actively involves students in the learning process through the stages of observation, understanding, planning, action, and evaluation. stages of observation, planning, implementation, and evaluation. The method of implementing the community service involves direct assistance to students in accessing and using hooda math. The evaluation results show that students are more motivated, active, and have increased skills in solving math problems